Phương pháp đối ngẫu giải bài toán điều khiển tối ưu tuyến tính với rang buộc dạng Alternative - Hà, Vũ Thanh (Journal of Computer Science and Cybernetics, 2016)
This paper is described in great detail algorithm for maximizing the subject function of the discrete control system with the alternative constrains following final points by the dual method. The algorithm is based on the plan notion that is firstly proposed by R.Gabasov and F.M. Kirillova in linear programming. The advantage of method is which do not known the initial acceptable controls.